Ciberbullying y su influencia en el rendimiento académico de los estudiantes de décimo año de educación básica de la Unidad Educativa Municipal Marcuard De Yerovi, cantón Salcedo, periodo mayo-septiembre 2023 - Cualchi Ulcuango, Juliana Fernanda (2024)
The research project focuses on exploring the relationship between cyberbullying and the academic performance of tenth grade students in the Alicia Marcuard de Yerovi Municipal Educational Unit, located in the Salcedo canton, during the period between May and September 2023, with the main objective of identifying how cyberbullying affects the academic performance of tenth grade students. The study will employ inductive and deductive research methods, as well as quantitative and qualitative approaches to obtain a complete understanding of the phenomenon, which will allow analyzing its impact on academic performance. Various research techniques and instruments will be used, including surveys, interviews, document analysis and observation sheets, with a mixed approach that will allow collecting data from different perspectives. The project seeks to contribute to the understanding of cyberbullying in the context of education and communication, in order to develop effective prevention and awareness communication strategies that promote a safe school environment conducive to learning. The research results are expected to provide a more complete understanding of the relationship between cyberbullying and students' academic performance, as well as insights into associated risk and protective factors.